2023
DOI: 10.1038/s41477-022-01338-0
|View full text |Cite
|
Sign up to set email alerts
|

Leaf transformation for efficient random integration and targeted genome modification in maize and sorghum

Abstract: Transformation in grass species has traditionally relied on immature embryos and has therefore been limited to a few major Poaceae crops. Other transformation explants, including leaf tissue, have been explored but with low success rates, which is one of the major factors hindering the broad application of genome editing for crop improvement. Recently, leaf transformation using morphogenic genes Wuschel2 (Wus2) and Babyboom (Bbm) has been successfully used for Cas9-mediated mutagenesis, but complex genome edit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 74 publications
0
31
0
1
Order By: Relevance
“…Recent studies have identified the basal leaf as an alternative explant for young embryos, and the use of a new promoter combination to enhance the expression of the morphogenetic genes Babyboom ( Bbm ) and Wuschel 2 ( Wus2 ) was able to obtain high transformation efficiency. This method is sufficient to support Cas9-mediated genomic modification techniques with success rates similar to those obtained with immature embryos, and this method demonstrates the advantages of basal leaves as starting explants, opening up new ways of sorghum transformation . In addition, techniques that bypass tissue culture offer new opportunities for rapid genome editing and refinement.…”
Section: Domestication and Breeding Of Sorghum In The Futurementioning
confidence: 86%
See 1 more Smart Citation
“…Recent studies have identified the basal leaf as an alternative explant for young embryos, and the use of a new promoter combination to enhance the expression of the morphogenetic genes Babyboom ( Bbm ) and Wuschel 2 ( Wus2 ) was able to obtain high transformation efficiency. This method is sufficient to support Cas9-mediated genomic modification techniques with success rates similar to those obtained with immature embryos, and this method demonstrates the advantages of basal leaves as starting explants, opening up new ways of sorghum transformation . In addition, techniques that bypass tissue culture offer new opportunities for rapid genome editing and refinement.…”
Section: Domestication and Breeding Of Sorghum In The Futurementioning
confidence: 86%
“…This method is sufficient to support Cas9-mediated genomic modification techniques with success rates similar to those obtained with immature embryos, and this method demonstrates the advantages of basal leaves as starting explants, opening up new ways of sorghum transformation. 123 In addition, techniques that bypass tissue culture offer new opportunities for rapid genome editing and refinement. In this method, the junction of plant rhizomes was cut under nonsterile conditions, and the upper part was infected with Agrobacterium rhizomes, then cultured on vermiculite medium, and the positive new roots were taken, cut into segments and then cultured, to obtain stable transformation of regenerated transformation plants.…”
Section: Domestication and Breeding Of Sorghum In The Futurementioning
confidence: 99%
“…This challenge can be overcome using a recently demonstrated approach that enabled de novo formation of transgenic shoot tissue via agrobacterium‐based delivery of plant developmental regulator genes to both explants and adult dicot plants (Maher et al ., 2020). Similarly, the delivery of developmental regulator genes has been recently demonstrated to enable de novo generation of large numbers of somatic embryos from leaf tissue in monocots (Wang et al ., 2023).…”
Section: Circumventing Generation Time Bottlenecks Using Chimeras And...mentioning
confidence: 99%
“…(2) Pesticide spraying can effectively control maize diseases and pests, but some studies have demonstrated that even registered and widely used safety pesticides can cause environmental pollution when improperly applied . (3) Gene editing technology can enhance maize resistance to diseases, pests, and disasters . However, this technology is time-consuming and raises biosafety concerns.…”
Section: Introductionmentioning
confidence: 99%
“…4 (3) Gene editing technology can enhance maize resistance to diseases, pests, and disasters. 5 However, this technology is time-consuming and raises biosafety concerns. (4) Foliar fertilizers, 6 such as ZnO, 7 can promote nutrient absorption by enhancing metabolization; however, their efficiency needs improvement.…”
Section: Introductionmentioning
confidence: 99%